EFFORTS TO MINIMIZE STRESS IN ADOLESCENTS THROUGH GOING FOR COFFEE "NGOPI" IN MALANG CITY - Windi Chusniah Rachmawati; Fitri Khalimiah; Endang Sri Redjeki (The Indonesian Journal of Public Health, 2021)
There are a large number of teenagers in the world who experience mental health problems as a result of stress, which disrupts human productivity. A good mental state allows people to realize the potential that exists in themselves, overcome the stresses of life, work productively, and contribute to their community. The purpose of this study was to describe efforts to minimize stress among adolescents by going for coffee in Malang city. This research was descriptive with a quantitative approach. Data was obtained through direct observation and interviews with respondents based on research guidelines. Stress minimization refers to the reduction of stress or actions taken when experiencing stress to calm the mind, which can be done by seeking peace, drinking coffee, and hanging out with friends. Managing stress in adolescents is important because it will affect the next stage of their lives. If adolescents cannot manage stress properly, they will continue to think about it and their performance will not be optimal. The attitude taken when having a problem that disturbs the mind can vary, such as worshipping first then looking for the source of the problem. Alternatively, taking a walk and drinking coffee can calm the mind. Doing assignments in a coffee shop rather than in a boarding house is more productive and allows for many ideas to arise.Keywords: stress, reducing stress, coffee shop, teenage age